Social capital as a determinant of quality of life in greek cancer patients: a cross-sectional study - Pitis, Athanasios; Diamantopoulou, Maria; Panagiotou, Aspasia; Papageorgiou, Dimitrios; Tzavella, Foteini (Frontiers in Public Health, 2025)
IntroductionHealth equity continues to be an obstacle in Greece. The EU Cancer Inequalities Registry indicates that social determinants of health significantly influence the cancer burden in Greece, thus affecting quality of life.MethodsThis was a cross-sectional study; the Social Capital Questionnaire Greek version was used for the evaluation of individual social capital, and the EORTC Core Quality of Life questionnaire (EORTC QLQ-C30) was used for the assessment of quality of life. The Kolmogorov–Smirnov test was used for checking the normality distribution of the quantitative variables. Quantitative variables were expressed as mean values (Standard Deviation) and as median (interquartile range), while categorical variables were expressed as absolute and relative frequencies. The association between QoL and Social capital scales was checked via Spearman correlation coefficients (rho).ResultsGreater total score in Social capital scale was significantly associated with greater overall QoL (β = 0.005; p < 0.001), better Emotional functioning (β = 0.004; p = 0.004) and better Social functioning (β = 0.009; p = 0.002),with lower Nausea and vomiting (β = −0.017; p = 0.015), Insomnia (β = −0.014; p = 0.002), Appetite loss (β = −0.010; p = 0.018) and Constipation symptoms (β = −0.009; p = 0.047).ConclusionThere was a strong association between a greater social capital score and the quality of life of Greek cancer patients, indicating that higher levels of social capital are associated with improved quality of life.